Health Information System (Hospital Billing System) / Agnesia A. Sapati - Agnesia, A. Sapati (2003)
The project proposal contained herein encompasses the system analysis and literature review of the billing module. It details the software and hardware involved, including discussions on why certain configurations are favoured over other. The reader will find that this proposal also contains the methodology used for the system's development. The methodology discussed is based on basic software engineering principles and will be applied throughout the development phases of the system which will consist of system analysis, design, implementation, testing and so on. The billing module will be used to issue bills to the patients for payment. Extensive research and background surveys on all topics involved have been made prior to the preparation of this proposal. This has been done to ensure o higher level of accuracy in the designing process, along with a better knowledge base to begin with when actual system development begins. It is hoped that users will find this proposal an informative document regarding the system which is to be developed later.